2016
DOI: 10.1080/21551197.2016.1247022
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Diet Quality, and Mortality among Community-Dwelling Prefrail and Frail Older Adults

Abstract: It is unknown if physical activity and diet quality are associated with the risk of poor outcomes, such as mortality, among prefrail and frail older adults. This was a population-based cohort study among 1,487 prefrail and frail older-adults from the Third National Health and Nutrition Survey. Compared to participants who were sedentary (0 bouts of physical activity per week), those who were physically inactive (1–4 bouts of physical activity per week) were 24% less likely to die [HR: 0.76 (95% CI: 0.58–0.98)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Results of our current study are also consistent with our earlier study including older persons aged 65 years and older that was of shorter duration (mean follow‐up of 3.1 years) with fewer incident mortalities and found that low diet quality was associated with higher mortality risk . Other observational studies have also found that adherence to a healthy diet, assessed by the Healthy Eating Index (HEI), the Mediterranean diet score, and other indexes, was associated with lower risk of mortality in prefrail and frail older persons as well as older adults with sarcopenia . However, some studies examining the relationships between dietary pattern, diet quality, and mortality among older persons in observational studies revealed inconclusive results .…”
Section: Discussionsupporting
confidence: 91%
“…Results of our current study are also consistent with our earlier study including older persons aged 65 years and older that was of shorter duration (mean follow‐up of 3.1 years) with fewer incident mortalities and found that low diet quality was associated with higher mortality risk . Other observational studies have also found that adherence to a healthy diet, assessed by the Healthy Eating Index (HEI), the Mediterranean diet score, and other indexes, was associated with lower risk of mortality in prefrail and frail older persons as well as older adults with sarcopenia . However, some studies examining the relationships between dietary pattern, diet quality, and mortality among older persons in observational studies revealed inconclusive results .…”
Section: Discussionsupporting
confidence: 91%
“…After dual screening, 11 547 relevant studies were identified. The body of evidence included 153 articles (involving 6 550 664 individuals), of which 1 was from a randomized clinical trial (RCT) 18 and 152 were from observational studies 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Resultsmentioning
confidence: 99%
“…Studies enrolled adults and older adults (aged 17-84 years at baseline) from 28 countries with a high or very high Human Development Index 16 classification (Australia, Belgium, Canada, Czech Republic, Croatia, Denmark, Finland, France, Germany, Greece, Hong Kong, Hungary, Iran, Italy, Japan, Korea, Norway, Netherlands, Poland, Portugal, Russia, Serbia, Singapore, Spain, Sweden, Switzerland, United Kingdom, and United States). Fifty-three studies 21 , 23 , 24 , 27 , 29 , 32 , 33 , 37 , 39 , 40 , 42 , 43 , 44 , 46 , 47 , 52 , 56 , 57 , 58 , 59 , 60 , 61 , 72 , 73 , 74 , 78 , 83 , 86 , 94 , 95 , 96 , 98 , 100 , 101 , 102 , 104 , 107 , 110 , 118 , 125 , 126 , 127 , 129 , 135 , 137 , 150 , 158 , 160 , 161 , 163 , 166 originated from the US. Some studies exclusively enrolled female 29 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations